Pemberdayaan UMKM Jamu Oemah Rempah melalui Penerapan Teknologi Tepat Guna untuk Meningkatkan Efisiensi Produksi dan Kualitas Produk di Kabupaten Sukoharjo - Mohamad Harisudin; Kusnandar; Erlyna Wida Riptanti; Nuning Setyowati; Raden Rara Aulia Qonita; Isti Khomah; Nur Wulan Sari Adha; Dinda Annisa Nur Hidayati; Annida Kharisma Putri; Dhea Ananda Widiyani; Triana Nurul Rizq (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the production capacity and operational efficiency of Oemah Rempah Herbal Medicine MSME through the implementation of appropriate technology tailored to the partner's needs. The program adopted a participatory approach consisting of needs identification, technology introduction and implementation, training and mentoring, as well as monitoring and evaluation. The collected data were analyzed using descriptive comparative analysis. The results demonstrated that the implementation of appropriate technology had a positive impact on the partner's production process. The use of a high-speed blender accelerated the grinding of herbal raw materials, resulting in a more efficient process and finer particle sizes that enhanced the extraction of bioactive compounds. In addition, the rose burner gas stove improved the efficiency and effectiveness of the herbal cooking process, while the cup sealer produced packaging that was more secure, hygienic, and visually appealing. Overall, the participatory implementation of appropriate technology contributed to improved production efficiency, enhanced packaging quality, and increased production capacity of the Oemah Rempah Herbal Medicine MSME in Sukoharjo Regency.